Local Wisdom in Kebangru'an Rites in Pringgabaya East Lombok - Sosani, Yuga Anggana (Sophist : Jurnal Sosial Politik Kajian Islam dan Tafsir, 2023)
This paper discusses the local wisdom in the Kebangru'an rite, a traditional procession of the people of Pringgabaya District, East Lombok Regency in overcoming trance disorders. The method used is qualitative ethnography where the researcher is involved and interacts directly in in the community whom is the object of research, to find out the historical value, form of presentation, local wisdom and challenges in the entire series of Kebangru'an Rites. Data collection was conducted by means of observation and in-depth interviews. Observations were made by observing various actions that were patterned and reflected the thinking system of the Kebangru'an Rite activists which included speech, expressions, statements, perspectives on life, and their life history. The results show that as a sacred ritual, the Kebangru'an Rite is identical to the ancient belief of animism. The form of the Kebangru'an Rite is dominated by elements of art: dance and musical accompaniment. A possessed person will dance endlessly to the music of Kebangru'an. Ritus Kebangru'an has its own wisdom for the supporting community: (1) as a medium of transcendental communication between the community and ancestral spirits, (2) as an expression of tradition that contains messages about the description of the cycle of life to death. The wisdom values contained in the Kebangru'an Rite are: (1) as a healing therapy for people in trance, (2) as a source of information from ancestral spirits, (3) as a medium of alternative medicine for the community, (4) foster a sense of concern for others, (5) foster an attitude of mutual cooperation, (6) foster an attitude of discipline and order, and (7) improve religious attitudes. Meanwhile, threats to the sustainability of the Kebangru'an Rite arise from three groups: (1) Ultra modernists who consider that traditional ritual offerings to be something old-fashioned, (2) Puritan religious groups who view the Kebangru'an Rite as a form of shirk and contrary to Islamic teachings. (3) Pragmatic attitudes, namely those who think practically, quickly and instantaneously.